Determination of retained tritium from ILW dust particles in JET. (January 2020) - Ashikawa, N.; Torikai, Y.; Asakura, N.; Otsuka, T.; Widdowson, A.; Rubel, M.; Oyaizu, M.; Hara, M.; Masuzaki, S.; Isobe, K.; Hatano, Y.; Heinola, K.; et al.
Highlights: Quantitative tritium analyses, full combustion and liquid scintillography, in fusion dust particles were performed for the first time. Similar levels of specific tritium inventory were observed in carbon wall and ILW-1, due to remained carbon dust from CFC divertor in the ILW dust. Total tritium inventory in dust particles, 0.6  GBq, after the first ILW campaign was 450 times less than from the JET-C operation: 2.7 × 10 2  GBq. Abstract: Quantitative tritium inventory in dust particles from campaigns in the JET tokamak with the carbon wall (2007–2009) and the ITER-like wall (ILW 2011–2012) were determined by the liquid scintillation counter and the full combustion method. A feature of this full combustion method is that dust particles were covered by a tin (Sn) which reached 2100 K during combustion under oxygen flow. The specific tritium inventory for samples from JET with carbon and with metal walls was measured and found to be similar. However, the total tritium inventory in dust particles from the ILW experiment was significantly smaller in comparison to the carbon wall due to the lower amount of dust particles generated in the presence of metal walls.